(untitled) (Theatrum historiae, 2022)
The aim of the paper is to analyse the activities of the Imperial Envoy Count Karl Ludwig von Ficquelmont in the Russian Empire during the first half of the nineteenth century, with a special emphasis on his salon in St. Petersburg. This salon, which Ficquelmont ran in the years 1829–1840 with his Russian wife Darya Fyodorovna (Dolly), was located in the building of the Austrian Embassy in St. Petersburg and was the centre of not only cultural but also diplomatic life in the Russian capital. Interestingly, the cultural and artistic level was combined with the diplomatic and political level, which testifies to Ficquelmont as a host with a truly broad intellectual scope. The paper examines how these levels interacted, while pointing out that Ficquelmont made extensive use of his privileges as an influential diplomat and one who was loved at the court to help guests in his salon circumvent some Russian obstructions, including the severe censorship of that time. Ficquelmont’s most famous guest was the poet Alexander Sergeyevich Pushkin, who gained inspiration from the Austrian Embassy building for one of his famous works. In addition, Ficquelmont has connections with the Czech lands, as he and his wife are buried in Teplice, where his daughter married. Overall, the aim is to introduce Count Ficquelmont as an educated and cultured diplomat who naturally ran one of the most influential Russian salons of the first half of the nineteenth century. Within the source base, diplomatic reports (Ficquelmont sought greater rapprochement of the Austrian Empire with the Russian Empire) as well as various ego-documents, including the extensive diary of Darya Fyodorovna von Ficquelmont, and, marginally, contemporary Russian fiction are used equally. It was the salons that provided a large number of stimuli for the formation of Russian culture, and it was here that important socio-cultural topics of the time were discussed. It can thus be stated that the salons stood at the very birth and beginnings of Russian public opinion.